Aesthetically Designing Video-Call Technology With Care Home Residents: A Focus Group Study - Zamir, Sonam; Allman, Felicity; Hennessy, Catherine Hagan; Taylor, Adrian Haffner; Jones, Ray Brian (Frontiers in Psychology, 2021)
Background: Video-calls have proven to be useful for older care home residents in improving socialisation and reducing loneliness. Nonetheless, to facilitate the acceptability and usability of a new technological intervention, especially among people with dementia, there is a need for user-led design improvements. The current study conducted focus groups with an embedded activity with older people to allow for a person-centred design of a video-call intervention. Methods: Twenty-eight residents across four care homes in the South West of England participated in focus groups to aesthetically personalise and ‘dress-up’ the equipment used in a video-call intervention. Each care home was provided with a ‘Skype on Wheels’ (SoW) device, a wheelable ‘chassis’ comprising an iPad or tablet for access to Skype, and a telephone handset. During the focus group, residents were encouraged to participate in an activity using colourful materials to ‘dress-up’ SoW. Comments before, during and after the ‘dress up’ activity were audio recorded. Framework analysis was used to analyse the focus group data. Results: Older people, including seven with dementia were able to interact with and implement design changes to SoW through aesthetic personalisation. Themes arising from the data included estrangement, anthormorphism, reminiscence, person centred personalisation, need for socialisation versus fear of socialisation and attitudes towards technology. After this brief exposure to SoW, residents expressed the likelihood of using video-calls for socialisation in the future. Conclusions: Care home residents enjoy engaging with new technologies when given the opportunity to interact with it, to personalise it and to understand its purpose. Cost-effective aesthetic personalisation of technologies can improve their acceptability, usability, and implementation within complex care environments.